The Impact of Regional Revenue Structures on Regional Financial Independence: Evidence from Banten Province - Lira Diandra; Haryanto Haryanto (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to analyze the regional financial independence. Regional financial independence is measured by the influence of regional revenue structures, which include PAD, DAU, DAK, and DBH. The method used in this study is multiple linear regression data covering 4 regencies and 4 cities in Banten Province over 6 years (2019-2024), yielding a total of 48 observations. The results show that PAD positively influences the regional financial independence. In-depth analysis reveals that this positive influence is driven primarily by Local Tax Revenue, which accounts for most regional revenue, with a sharp disparity in contributions between city and regency areas. Conversely, all transfer revenue components (DAU, DAK, and DBH) negatively affect regional financial independence. These findings indicate that high central government fund flows reduce regional incentives to optimize their independent fiscal potential. Local governments are advised to reduce their dependence on transfer revenue by optimizing Local Taxes through policies that strengthen the local tax base, a crucial step toward achieving sustainable financial independence.